Human rights : a very short introduction - Clapham, Andrew (2015)
Today it is usually not long before a problem gets expressed as a human rights issue. Indeed, human rights law continues to gain increasing attention internationally, and must move quickly in order to keep up with a social world that changes so rapidly. This book, in its second edition, brings the issue of human rights up to date, considering the current controversies surrounding the movement. Discussing torture and arbitrary detention in the context of counter terrorism, Andrew Clapham also considers new challenges to human rights in the context of privacy, equality and the right to health. Looking at the philosophical justification for rights, the historical origins of human rights and how they are formed in law, Clapham explains what our human rights actually are, what they might be, and where the human rights movement is heading.
Looking at rights -- Historical development and contemporary concerns -- Human rights foreign policy and the role of the United Nations -- Torture -- Deprivations of life and liberty -- Balancing rights: free speech and privacy -- Food, education, health, housing and work -- Discrimination and equality -- The death penalty.
"Fully updated new edition"--Cover.
Includes bibliographical references (pages 169-183) and index.
Keywords: Human rights; International law and human rights; Respect for persons; Human rights; International law and human rights; Respect for persons